Salivary and Serum Aspartate Aminotransferase and Alanine Aminotransferase in An Uncontrolled Diabetic Patients - Dunya malhan henweet1, Amina Ryhan Diajal2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Diabetes mellitus (DM) is a metabolic disorder, characterized by a higher level of blood glucose resulted from either abnormality in insulin production (type1 DM) or resistance to insulin action (type 2 DM) or both. Long lasting elevated blood glucose is responsible for chronic damage, defect in function and impairment of various organs including salivary glands. Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) are cellular enzymes found in all animal tissues. Aims of the Study: to estimate and compare the levels of salivary and serum AST and ALT between un controlled diabetic patients and normal control people. Subjects, Materials and Method: The study comprised 90 adults of both gender. The patients were divided into 3 groups: 30 patients with type 1 diabetics (D1), 30 patients with type 2 diabetics (D2) and 30 healthy persons as a control group (C). Serum and un stimulated salivary samples were taking for the AST, ALT evaluating using standard spectrophotometer kits. The level of glycosylated hemoglobin (HbA1c) was measured using NycoCard kit to exclude the controlled diabetic patients. Data were analyzed using statistical analysis SPSS version 24. Results: The results showed a significant increase of salivary enzymes in D1 and D2 compared to salivary enzymes of control group, while there was no significant difference in serum enzymes value among all studied groups. Conclusions: An elevation in salivary AST and ALT in both types of diabetes compared to healthy group, with higher salivary level of AST and ALT in D1 compared to D2 and to healthy control group. This may suggest that autoimmunological activity in D1 responsible for more salivary gland injury in D1 group.